Mitigation of the Interplay Effects of Combining 4D Robust With Layer Repainting Techniques in Proton-Based SBRT for Patients With Early-Stage Non-small Cell Lung Cancer - Wei, Long; Shang, Haijiao; Jin, Fu; Wang, Yuenan (Frontiers in Oncology, 2020)
Objective The objective of this study was to evaluate the interplay effects in proton-based stereotactic body radiotherapy (SBRT) using 4D robust optimization combined with iso-energy layer repainting techniques for non-small cell lung cancer (NSCLC). Materials and Methods Twelve patients with early-stage NSCLC who underwent 4DCT were retrospectively selected. A robust CTV-based 4D plan was generated for each based on commercial Treatment planning system (TPS), considering patient setup errors, range uncertainties, and organ motion. The 4D static dose (4DSD) and 4D dynamic dose (4DDD) were calculated using a hybrid deformable algorithm and simulated proton delivery system. An index ΔIMR(%) was developed to quantitatively evaluate the interplay effects. The interplay effects of the 4D robust plan and multiple iso-energy layers (3, 4, 5, 6, and 7) of the robust repainting 4D plan were calculated based on ΔIMR(%) to select the optimal times for layer repainting. Results Due to the interplay effects, the mean target values D2 and D5 increased to 1.28 and 1.01%, and the target values D98 and D95 decreased to 2.01 and 1.77%, respectively, for the 4D Robust SBRT plan. After multiple iso-energy repainting times, the interplay effects of the target values D98 and D95 tended to migrate, from 2.01 to 0.92% in target value D98 and from 1.77 to 0.89% in target value D95, respectively. Moreover, a positive linear correlation was observed between the optimal interplay effect mitigation and target range of motion. Conclusion In proton-based 4D Robust SBRT, the interplay effects degraded the target dose distribution but were mitigated using iso-energy layer repainting techniques. However, there was no significant correlation between the number of repainting layers and improvements in the dose distributions. The optimal layer repainting times based on the interplay effect index were ascertained according to the patient characteristics.